Automation of the monitoring system for surface contamination with [alpha]-active radionuclides; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Khan V. A. Valery Alekseevich; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khorokhorin D. M.; Izhoykin D. A.; Kuznetsov M. S. Mikhail Sergeyevich; Panamareva A. N. Anna Nikolaevna; Rakhimzhanova A. (2021, 2021)
Title screen